Carotid Endarterectomy for the Treatment of Carotid Near-Occlusion With Recurrent Symptoms - Zhang, Jianbin; Chen, Jie; Xu, Xiaojie; Sun, Mingsheng; Chen, Shu; Liu, Peng; Ye, Zhidong (Frontiers in Neurology, 2022)
Objective Report our preliminary experience of carotid endarterectomy (CEA) for the treatment of carotid near-occlusion (CNO) with recurrent symptoms. Materials and Methods Retrospectively analyze the demographics, treatment detail, and outcomes data of 122 patients with CNO from 2014 to 2020. According to whether distal full collapse exists, patients were classified into the full collapse group and the non-full collapse group. The incidence of death, myocardial infarction, stroke, and other variables were compared between the two groups. Results A total of 122 patients with CNO and recurrent symptoms were enrolled. The demographics were comparable between the two groups. Thirty-day incidence of primary endpoints was 1.85% in the full collapse group and 4.41% in the non-full collapse group. Twelve-month incidence of primary endpoints was 7.41% in the full collapse group and 4.41% in the non-full collapse group. One re-stenosis occurred in the non-full collapse group 8 months after CEA. Conclusion For patients with CNO with recurrent symptoms, CEA is not worse than the results described in historical control groups, despite whether distal full collapse exists. The shunt is important to avoid intraoperative hypoperfusion and postoperative hyperperfusion. The long-term results should be further evaluated.